Bangladesh RMG Supply Chain Vulnerabilities To Disruption Beyond Covid-19 - Tusher, Nayem Uddin Hoque (International Research Journal of Business Studies, 2021)
With the recent outbreak of Covid-19, the fragility of the global SC has been revealed. Significant disruption from both the demand and supply side has jolted the garment industry of Bangladesh. This paper aims to foster a more explicit understanding of the disruption vulnerability factors of the Bangladesh RMG SC beyond Covid-19. To achieve this aim, an exploratory study methodology is used by extensive literature review. Analysis revealed that Bangladesh RMG SC is vulnerable to hazard, strategic, financial, operational, infrastructural, and demand and supply factors. Natural calamities, infrastructural collusions, labor and political unrest, globally intensified competition, non-compliance issues, high dependency on imported materials, lack of product, and market diversification can lead Bangladesh RMG SC to disruptive events. The analysis of this study will help factory owners, industrial managers, and designated authorities to identify vulnerabilities associated with the Bangladesh RMG SC and take measures to reduce the vulnerabilities to disruption.